(untitled) (Journal of Educational Sciences, 2025)
The focus on innovative development of the modern economy determines the need to rely on professionals ready for innovative activity. This is especially important when it comes to today’s students - tomorrow’s teachers. Despite the interest of scientists and practicing teachers in developing the readiness for innovative activity of university graduates, an open question still remains the lack of clear ideas about the real level of innovativeness of modern students, as well as about the factors that can be significant for its manifestation in the context of professional practice. The purpose of the study: to form an objective idea of the readiness for innovative activity of university graduates - future teachers of mathematics and computer science and to identify the factors that can affect their innovative professional activity. The implementation of the designated goal was carried out on the basis of the analysis of scientific sources, questionnaires of students and teachers, methods of statistical processing of the survey results. The conducted study allowed us to establish that the level of their readiness for innovative professional activity of future teachers only slightly exceeds the average. The theoretical significance of the study lies in the detailed analysis and systematization of the terminological field of the problem under consideration. The practical significance of the study lies in determining the components of the educational environment of a modern university, which will contribute to the development of students’ innovativeness. Key words: innovative activity, innovativeness, teacher training at a university, innovative educational environment.